2022
DOI: 10.3390/su14148468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erosion Micro-Topographies on Plant Colonization on Weathered Gangue Dumps in Northeast China

Abstract: Micro-topography has been proved to be beneficial for plant colonization in severe environments. There are numerous micro-topographies caused by erosion of gangue dumps in the Northeast China, which can make plant colonization difficult. To determine how these micro-topographies affect plant colonization, the environment conditions, regeneration characteristics, vegetation characteristics of different erosion micro-topographies, such as bare slope, rill, ephemeral gully and deposit body were studied, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…However, our previous research showed that although the environmental conditions were inadequate for plant colonization on most parts of the waste dumps, some plants were able to colonize and distribute in discrete areas. This indicates that some erosion micro-topographies can drive plant colonization (Wang et al, 2022). Similar results were also found on other waste dumps in this research.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, our previous research showed that although the environmental conditions were inadequate for plant colonization on most parts of the waste dumps, some plants were able to colonize and distribute in discrete areas. This indicates that some erosion micro-topographies can drive plant colonization (Wang et al, 2022). Similar results were also found on other waste dumps in this research.…”
Section: Introductionsupporting
confidence: 89%
“…The mechanical composition was determined by calculating the content percentage of each particle group using the drainage method. The substrate particles were classified according to the characteristic substrate particle size of the waste dumps (Wang et al, 2022) as fine grain (particle size <2 mm), middle-coarse grain (particle size between 2 and 10 mm), coarse grain (particle size between 10 and 20 mm), and giant grain (particle size >20 mm).…”
Section: Determination Of Substrate Physicochemical Propertiesmentioning
confidence: 99%